A comparative analysis between recreational and artisanal fisheries in a Mediterranean coastal area. (28th January 2013) - Lloret, J.; Font, T.
Abstract The biological impact and the social characteristics of different artisanal (professional) and recreational fishing techniques on the marine resources of a coastal Mediterranean area were compared. Data were from artisanal and recreational surveys carried out between 2006 and 2010. Competition between recreational (particularly spear fishing) and artisanal fishers for the natural resources is important as 52% of the 98 species surveyed were caught by both types of fishers. A total of 87 species were caught by all artisanal fishing gears together (of which 84% were retained and 16% discarded). Recreational fishing caught 58 species of which none was systematically discarded. The two fishing techniques that raise major environmental concerns are spear fishing (very selective in terms of species and/or sizes and high intrinsic vulnerability of catches) and trammel netting (highest number of species discarded and highest number of species endangered). Important challenges from the social standpoint were found that need to be taken into account in the management of coastal fisheries in the Mediterranean Sea including: progressive disappearance of the artisanal fisheries, ageing of the artisanal fisher populations and decline in the number of fishing gears used by artisanal fishers.